The Impact of Implementing Organizational Change Strategies on Achieving Strategic Success: An Applied Study at Princess Sumaya University for Technology in Jordan - Omari, Mohammad; Alomari, Mohammad Ibrahim; Abuqauod, Ghazi Rasmi (International Journal of Membrane Science and Technology, 2023)
The aim of this study was to investigate the impact of applying organizational change strategies on achieving strategic success. The study was conducted at Princess Sumaya University for Technology in Jordan using a descriptive-analytical methodology. The study population consisted of all employees in the university, totaling 300 workers from upper, middle, and lower management. A sample was selected using the stratified sampling method, representing 56.3% of the workers, or 169 subjects. To achieve the study objectives, a questionnaire was designed to collect data, which was distributed to the participants electronically. After retrieving the questionnaires, 7 were excluded for being invalid for statistical analysis purposes. The final sample size was 162 workers, representing 95.8% of the main sample. Descriptive statistical methods were used, including frequencies, percentages, Cronbach's alpha test, mean and standard deviation, and multiple linear regression, within the Statistical Package for the Social Sciences (SPSS). The study found that the dimensions of organizational change strategies were available and practiced collectively at a high level in Princess Sumaya University for Technology, and the dimensions of strategic success were also at a high level. The study recommended enhancing the concept of strategic change in the university, promoting the use of scientific research methods to help generate new knowledge and skills for university workers, increasing attention to skilled workers, creating a suitable climate to encourage them to stay and continue working, and enhancing the role of university management in activating strategic risk management to improve the university's strategic performance.